Granulometric Study of the Lokoja Sandstone, Mid Niger Basin, Nigeria - Madukwe, Henry Y (Review of Environment and Earth Sciences, 2017)
Grain size studies of the Campanian-Maastrichtian Lokoja Formation have been investigated. The sand particles exhibit low sphericity which are angular to sub-angular. Histograms showed unimodal and bimodal trends and is predominantly asymmetrical with varying modal class, which may be due to variation in transporting medium energy. The graphic mean ranges from 0.1ф (coarse grained) to 1.35ф (medium grained) while the is average 0.81ф (coarse grained). The dominance of coarse grained particles and dearth of fine sands implies strong to moderate energy conditions during deposition. The standard deviation ranges from 0.08ф-0.60ф (very well sorted to moderately well sorted); average of 0.40ф (well sorted), which may be due to rapid back and forth movement of the depositing medium. The skewness ranges between -0.39 and 0.59 (strongly coarse skewed to strongly fine skewed), while the graphic kurtosis ranges between 0.77 and 2.5 indicating playtykurtic to very leptokurtic and this variation may be due to some of the deposits being sorted in high-energy environment elsewhere. A Bivariate plot (simple skewness vs. standard deviation) shows the samples plotting mainly in the river sand zone. Another plot of mean size vs. standard deviation also shows the samples appearing in the river sand zone; other granulometric parameters that discriminates between river channel deposits, overbank deposits and overbank-pool deposits shows that the Lokoja sandstones plotted in the river channel zone. Linear discriminant analyses signpost a shallow marine beach environment. From the Passega diagram, majority of the samples plotted outside the featured fields, only three samples plotted within the diagnostic parameter zone around the uniform suspension-SR zone.